Why do indiviuals with schizophrenia drop out of observational clinical trials?. (October 2017) - Hofer, Alex; Radner, Verena; Edlinger, Monika; Kemmler, Georg; Rettenbacher, Maria A.; Fleischhacker, W. Wolfgang
Abstract: Randomized controlled trials (RCTs) and observational studies frequently differ with regard to study dropouts. The present naturalistic follow-up investigation aimed to shed a light on this issue by evaluating the time to and the reasons for study dropout in patients suffering from schizophrenia who started monotherapy with an oral new-generation antipsychotic. To this end, psychopathological symptoms and safety data were assessed in 194 patients who were followed up to a maximum observation period of twelve months. 9.3% of study participants completed the study. The mean time to study dropout was 2.6 ± 2.7 months with almost two thirds of patients dropping out within three months. 44.3% discontinued medication at the date of study dropout, the remainders dropped out due to withdrawal of written consent, logistic reasons, or nonappearance to the study visit ("loss to follow-up"), which were not necessarily to be equated with cessation of the antipsychotic. These findings indicate that in contrast to RCTs, dropout of observational studies is not necessarily associated with drug discontinuation. Accordingly, systematic differences between trial designs need to be considered when interpreting the results of clinical trials. Highlights: Out of 194 schizophrenia patients starting treatment only 9.3% continued on treatment beyond twelve months. The mean time to study dropout was 2.6 ± 2.7 months with almost two thirds of patients dropping out within three months. 44.3% of study participants discontinued medication at the date of study dropout. Dropout of observational studies is not necessarily associated with drug discontinuation. Systematic differences between trial designs need to be considered when interpreting the results of clinical trials.